Investigação de dopantes íons terras raras nos compostos ortofosfatos KMPO4 (M= Ba e Sr) - Barbosa Júnior, Gilberto José (2021)
KMPO4 (M = Ba and Sr) orthophosphates belong to an important group of luminescent materials, which have a wide range of optical applications when doped with the rare-earthions Yb, Dy, Tb, Eu, Sm, Pr, and Ce. These materials can be efficiently excited in the near ultraviolet (NUV) region and may present emissions in the visible or near-infrared (NIR) region, depending on the dopant to be used. For these properties and for the fact that experimental works generally do not describe the defect mechanisms that contribute to greater luminescence efficiency in these structures, due to the limitations of obtaining this information in experimental measurements, it was necessary to analyze the structures of pure KMPO4 (M = Ba and Sr) orthophosphates doped with rare-earth ions trivalent RE3+ (RE = Yb, Dy, Tb, Eu, Sm, Pr, and Ce) and divalent Eu2+, via simulation atomistic. With this modeling structural and defect properties were obtained. Thus, a new set of interatomic potential parameters was obtained to reproduce the structures of these compounds, which showed good agreement with experimental data in the literature. Then, intrinsic defects mechanisms and incorporation of trivalent RE3+ (RE = Yb, Dy, Tb, Eu, Sm, Pr, and Ce) and divalent Eu2+, and its consequences were investigated in KBaPO4 and KSrPO4. It was observed that, in the pure compounds, the most favorable intrinsic defects were the KM'+MK(M = Ba and Sr) anti-site and the potassium Frenkel defect. Furthermore, the results suggest that the probable incorporation of dopants is at the divalent site (Ba/Sr). It is predicted that intrinsic defects to neutralize the excess charge generated by trivalent dopants is the KMʼ anti-site, as it has a lower energy cost. The reduction processes of europium (Eu3+ -> Eu2+) were also investigated considering four reduction-doping processes (the open atmospheres, CO, N2, and H2). In this case, CO reducing atmosphere is the most effective agent for Eu reduction. It is observed that intrinsic defects, the preferred incorporation sites, and charge compensation mechanisms are directly associated with the luminescent properties of these orthophosphates.